Perilaku Petani terhadap Program Gerbang Pangan Serasi (Kasus di Subak Tajen, Desa Tajen, Kecamatan Penebel, Kabupaten Tabanan) - GUNAWAN, AGUNG PUTRA INDRA; SUARDI, I DEWA PUTU OKA; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017DO - 10.24843/JAA.2017.v06.i04.p12, 2017)
Farmer Behavior towards the Program of Gerbang Pangan Serasi (A Case at Irrigation Organization of Subak Tajen, Village of Tajen, Penebel Sub-District, Regency of Tabanan) Continuous use of inorganic fertilizer for a long time has had a negative impact on soil and the environment. In order to maintain the existence of the agricultural sector and to implement the efforts towards organic agriculture, the local government of Tabanan Regency established a flagship program called the Gerbang Pangan Serasi (GPS) Program. This study aims to determine the behavior of farmers towards the Gerbang Pangan Serasi (GPS) Program, which is measured from the level of knowledge, attitude, and skills. The research was conducted in Subak Tajen, Tajen Village, Penebel Sub-District, Tabanan Regency. The selection of research site was done purposively. The population was the Subak Tajen members who received the Gerbang Pangan Serasi (GPS) Program as many as 34 people. With the census technique, 12 farmers who received the aid of cattle were taken as respondents, plus 12 farmers who did not receive the aid of cattle. Thus, the total number of respondents was 24 people. Based on the findings of the research, it is known that the behavior of farmers who received the aid of cattle towards the Gerbang Pangan Serasi Program is good category, with knowledge score of 3,91, attitude score of 4,08 and skill score of 4,82. Whereas, the behavior of farmers who did not receive the aid of cattle was in moderate category, with the knowledge score of 3,01, attitude score of 3,69 and skill of 2,78. Thus, the behavior of farmers who received cattle assistance is categorized as good category with the score of 3.94 and the behavior of farmers who did not get the aid of cattle is classified as moderate category with the score 3.35. Based on the findings, it is suggested to farmers that they should be willing to apply technology and innovation in the field of agriculture provided by extension workers, because the farmers will get new experiences to be applied in their farming.